2011
DOI: 10.1007/s00167-011-1645-3
|View full text |Cite
|
Sign up to set email alerts
|

ACL reconstruction: comparison between transtibial and anteromedial portal techniques

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 44 publications
1
46
1
1
Order By: Relevance
“…33,34 A number of researchers have suggested that anteromedial approaches or outside-in approaches (or both) can yield tunnels in more anatomic positions than transtibial approaches. [35][36][37][38][39][40][41][42] In an anatomic study of ACL attachment locations using 20 human cadaveric knees, Zantop et al 25 reported that the center of the femoral AM bundle was located along the Blumensaat line at a distance of 18.5% of the sagittal diameter of the femur and at 22.3% of the height measured perpendicular to the Blumensaat line. However, other studies reported these respective parameters with considerable variability, as follows: 26.4% and 25.3% in a radiographic study of 7 cadaveric specimens, 30 21% and 24% in an anatomic study of 22 cadaveric knees with intact ACLs, 43 21.7% and 33.2% in a 3D CT study of 8 cadaveric knees, 31 and 27.7% and 16.3% in a study of 71 patients who underwent ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 A number of researchers have suggested that anteromedial approaches or outside-in approaches (or both) can yield tunnels in more anatomic positions than transtibial approaches. [35][36][37][38][39][40][41][42] In an anatomic study of ACL attachment locations using 20 human cadaveric knees, Zantop et al 25 reported that the center of the femoral AM bundle was located along the Blumensaat line at a distance of 18.5% of the sagittal diameter of the femur and at 22.3% of the height measured perpendicular to the Blumensaat line. However, other studies reported these respective parameters with considerable variability, as follows: 26.4% and 25.3% in a radiographic study of 7 cadaveric specimens, 30 21% and 24% in an anatomic study of 22 cadaveric knees with intact ACLs, 43 21.7% and 33.2% in a 3D CT study of 8 cadaveric knees, 31 and 27.7% and 16.3% in a study of 71 patients who underwent ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they advocated that evaluation of the bone tunnel is more accurately done using computed tomography (CT) rather than plain radiographs. Silva et al 11 used the CT in their study to assess the tibial and femoral tunnels. They found that the AM portal technique places the femoral and tibial tunnels more centrally in the ACL footprint when compared with the TT technique.…”
Section: Tunnel Expansionmentioning
confidence: 99%
“…Thus, technical modifications to the transtibial technique have been described in an effort to improve femoral tunnel obliquity and restoration of the native femoral ACL foot print [14,24]. However, there are concerns about the ability to obtain the anatomical femoral ACL foot print with a transtibial technique [7,13,16,18,23,39,43,46].…”
Section: Introductionmentioning
confidence: 99%